Expansion and Compression of a Helicate with Central Diol Units as Stereocontrolling Moieties - Grüninger, Saskia; Mevissen, Christian; Rissanen, Kari; Ward, Jas S.; Albrecht, Markus (Organic Materials, 2022)
The dicatechol ester ligand 2-H4 forms the compressed helicate Li4[(2)3 Ti2] which upon removal of the internally bound lithium cations expands. In the compressed form, the chiral diol units control the stereochemistry of the complex which is lost upon expansion of the system.
Keywords: self-assembly; helicates; molecular switches; stereochemistry